Relationship Between the Dimensions of Quality of Work Life and General Health in Iranian Nurses - Khadijeh Asadi; Maryam Niknami; Masoumeh Jafari Asl; Ehsan Kazemnezhad Leyli (Journal of Holistic Nursing and Midwifery)
Introduction: Job and career is one of the social aspects that affects the health of individuals. Nurses spend much of their time at work in close contact with patients, so the quality of their working life can have a significant impact on their health. Objective: This study aimed to investigate the relationship of Quality of Work Life (QWL) dimensions and general health dimensions in Iranian nurses working in treatment and educational centers of Rasht City, Iran. Materials and Methods: This is an analytical cross-sectional study conducted on 404 nurses working in eight treatment and educational centers in Rasht, Iran. The samples were selected by stratified random sampling method. For collecting data, a demographic form, Brooks Quality of Nursing Work Life (QNWL) questionnaire, and Goldberg and Hillier s General Health Questionnaire (GHQ) were used. The obtained data were analyzed using descriptive statistics and inferential statistics of Spearman correlation, Chi-Squared tests, and multiple logistic regression analysis. Results: The majority of the studied nurses (55.4%) had desirable QWL and most of them (61.1%) were suspected of having health disorder. There was a significant and negative relationship between total nurses QWL scores and its dimensions with total nurses general health and its dimensions (P<0.001). Regression analysis results indicate that the first dimension (work life/home life, OR=3.581, P<0.001), second dimension (work schedule, OR=1.932, P=0.038), and the third dimension (work conditions, OR=1.879, P=0.05) were the predictors of the nurses general health. Conclusion: Since the highest relationship was between work life/home life and general health, hospital managers are recommended pay more attention to this dimension of QWL, and use appropriate strategies such as providing child care services (like kindergarten services) and reducing nurses working hours to improve nurses general health.